Data to Care Opportunities: An Evaluation of Persons Living With HIV Reported to Be "Current to Care" Without Current HIV-Related Labs. (1st September 2019) - Hart-Malloy, Rachel; Shrestha, Tarak; Pezzulo, Molly C.; Patterson, Wendy; Gunn, Jayleen K. L.; Johnson, Megan C.; Tesoriero, James M.
Abstract : Background: Data to care (D2C) is an effective strategy using HIV surveillance data to link/relink persons living with HIV into medical care. However, some appearing to be not in care (NIC) report being in care (persons "current to care"). Setting: New York State's Expanded Partner Services (ExPS) D2C program has identified many persons reported as "current to care." This evaluation describes these persons after 24 months of follow-up and identifies HIV-related laboratory-based testing patterns and results to determine whether this cohort could benefit from further programmatic intervention. Methodology: Data from ExPS assignments from September 2013 to May 2016 were used. Persons "current to care" were compared with persons NIC on demographics, subsequent HIV-related laboratory-based testing, and viral load suppression status. Persons "current to care" receiving subsequent HIV-related laboratory-based testing were compared with those who did not receive HIV-related labs. Results: Persons "current to care" significantly differed from persons NIC on demographics and subsequent HIV-related laboratory-based testing (82% of persons "current to care" had subsequent HIV-related labs, versus 99% of those NIC who were relinked to care). Persons "current to care" were more likely to be virally suppressed at their subsequent lab than persons NIC who were relinked to care (72% vs. 47%). Minor differences were noted for persons "current to care" receiving subsequent HIV-related labs compared with those who did not. Conclusions: Persons "current to care" reflect a unique cohort who might benefit from further programmatic intervention. Although most received additional HIV-related labs, some were without labs for the duration of follow-up.